Strategies In Managing Horticultural Businesses In Indonesia (Article Review) - Fikriman Fikriman; Fuji Kacaya Mita; Pitriani Pitriani (Baselang, 2023)
Indonesia is called an agrarian country because of its fertility, beauty, and natural wealth, the agricultural sector is one of the leading sectors in the economy where agriculture is a business activity that includes the cultivation of food crops, one of which is in the field of horticulture. This study aims to determine the strategy in the management, business development of horticultural products. In this review of the journal entitled "strategy in the management of horticultural businesses in Indonesia", several kinds of research methods were found, such as: (1) Descriptive analysis research method, namely, statistics used to analyze data by describing or describing the data used. has been collected as it is without intending to make generally accepted conclusions or generalizations, (2) Survey research methods, namely, data collection using questionnaires which are then carried out by respondents, (3) Location Quotien analysis research methods, namely, an analysis used as one of the basic economic model approaches, is relevant and can be used as a technique to identify the distribution of agricultural commodities.In general, horticultural commodities have a comparative advantage as well as a competitive advantage, but the comparative advantage parameter is lower than the competitive advantage. Competitive.